Provision Of Handouts At The End Of Lecture; An Effective Teaching And Learning Practice - Sohail, Shaherzad; Majeed, Hira; Dar, Lubna Raiz; Shahid, Adeela (Journal of Rawalpindi Medical College, 2024)
Abstract Objective: This study aims to find out the perceptions of students on handouts as learning material and their effectiveness as an instructional tool. Method: It was a descriptive cross-sectional study, conducted at Shalamar Medical and Dental College. The duration of the study was 6 months from (June 2022 to December 2022). A total of 185 students of MBBS participated in the study. A structured questionnaire prepared by the researcher was used for the collection of data. Data was entered and analysed using SPSS version 22. Results: A total of 187 students from third year, fourth year and final year MBBS participated in the study.77.7% of students maintained a positive response that handouts helped them develop a better understanding of the lecture. A total of 78.8% of students felt a sense of satisfaction when handouts of lectures were made available to them. 85.9% of the students, in our research, reported that handouts have proved to be helpful in the preparation for exams. This research showed that 82.3% of the students supported the proposition that teachers should provide their students with lecture handouts Conclusion: The study suggests that students have a positive attitude towards the provision of instructor-prepared handouts and they consider it as an effective tool to enhance their learning.